Revitalizaç\~ao de áreas centrais nas cidades brasileiras por meio da mobilizaç\~ao de investimentos privados - Vanessa Gapriotti Nadalin (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– In addition to concentrating historical heritage, city centers often concentrate greater accessibility, in terms of urban mobility, as they concentrate urban infrastructure. Repopulating the centers contributes to more compact and sustainable cities. A considerable portion of Brazilian cities are currently designing legislation to encourage the repopulation of centers and their renewal. In part, in response to the emptying of buildings that concentrated offices in the post-pandemic, in part to boost the local economy. In common, the most recent revitalization proposals consider that almost all the resources to fund these investments would come from the private sector. In this context, this work contributes by pointing out possible challenges that current and new city center renewal projects must face in order to achieve their objectives. It was noted two major challenges of the renewal projects already implemented. First, do not bet too much on the dynamics of appreciation of real estate in the renewed region, and make mistakes in how much urban added value can be captured from this appreciation. The other major challenge refers to how to guarantee human rights, especially adequate housing, to all those involved in the urban renewal process.
10419/284918
Keywords: R21; R31; D63; H40; O18; 330; city centres; urban renewal; urban management